Accounting and Economic Perspectives on Management Control Systems - Sachdeva, Dr. Lalit; Sharma, Dr. Ravinder (International Journal of Accounting and Economics Studies, 2025)
Management accounting and control systems (MACS) play a crucial role for managers as they help monitor and pinpoint any deviations from earnings targets. In this analysis, we delve into how MACS influences earnings management, which hasn't received much attention in previous studies. To bridge the gap between actual and target profitability, we expect—and indeed find—evidence that managers actively use MACS to steer the organization’s focus towards developing and implementing effective action plans. These are actual earnings management measures since they are triggered by pressures on earnings and are intended to move earnings closer to their predetermined critical values. Administration tools that the company uses to oversee its managers and staff fall under the umbrella of management accounting and control. These management accounting systems play a vital role in encouraging, tracking, evaluating, and even penalizing the behavior of managers and employees within organizations.